The Influence of Product Quality and Product Attributes on Purchase Intention of Powdered Breast Milk Service Mediated by Belief Systems - Razan, Muhammad; Nuraeni, Shimaditya (Journal of Consumer Studies and Applied Marketing, 2024)
This study explores the impact of product quality, product attributes, and belief systems on purchasing intentions for Mengasihi breast milk powder manufacturing services. The research utilized an online survey to gather data from 284 mothers residing in the Greater Bandung and Jabodetabek regions. Participants were selected based on their familiarity with powdered breast milk and their status as parents. The data was analyzed using Path Analysis to understand the relationships between the variables. The findings demonstrate that both the quality and attributes of powdered breast milk products significantly influence consumer purchasing intentions. These effects are observed both directly and indirectly through the mediation of consumer belief systems. Specifically, product quality and attributes positively affect purchasing intentions by enhancing perceived value and satisfaction. However, the belief system was found to have the most substantial impact on purchasing intentions. This suggests that consumers' pre-existing beliefs and values play a crucial role in shaping their decisions regarding breast milk powder. The study highlights the importance of understanding consumer belief systems in the context of marketing strategies. For Mengasihi, these insights suggest that improving product quality and clearly communicating product attributes can enhance consumer perceptions and intentions. Additionally, addressing and aligning with consumer belief systems is essential for building trust and increasing brand loyalty. By focusing on these areas, Mengasihi can develop more effective marketing strategies to enhance consumer awareness and strengthen its market position.